Analysis of E-Service Quality and E-Trust on E-Satisfaction of PLN Mobile App Users With Digital Marketing as a Mediating Variable (Case Study at PT. PLN UP3 Pematang Siantar) - Resignedly Hatoguan Pakpahan; Nurafrina Siregar; Mesra B (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study analyzes the influence of e-service quality and e-trust on the e-satisfaction of PLN Mobile app users, with digital marketing as a mediating variable at PT. PLN UP3 Pematang Siantar. This is a quantitative study using a survey approach, involving 220 respondents and analyzed using Partial Least Squares with SmartPLS. The results indicate that e-service quality and e-trust have a positive and significant effect on e-satisfaction. Both variables also have a positive and significant effect on digital marketing, which subsequently mediates their influence on user satisfaction. The R-square value for e-satisfaction of 0.589 indicates that 58.9% of the variation in user satisfaction is explained by e-service quality, e-trust, and digital marketing. These findings confirm that user satisfaction with the PLN Mobile app is influenced by service quality, user trust, and the effectiveness of digital marketing. This study also highlights the importance of interactive and educational digital communication strategies to enhance user understanding and engagement. The research findings are expected to provide practical insights for PLN to design feature improvements, build customer loyalty, and optimize digital service transformation.